Khat use and associated factors during pregnancy in eastern Ethiopia: A community-based cross-sectional study - Misgana, Tadesse; Tesfaye, Dejene; Alemu, Daniel; Gebremichael, Berhe; Tamiru, Dawit; Tariku, Mandaras; Weldesenbet, Adisu Birhanu; Dheresa, Merga (Frontiers in Global Women's Health, 2022)
Introduction: Khat chewing poses many health and health-related problems. It results in reproductive severe health problems among pregnant women and their infants. These problems include intrauterine growth retardation, low birth weight, and the impairment of fetal growth hence increased infant morbidity and mortality. However, little is known about khat use and its associated factors among pregnant women in the study area. Objective: This study aimed to assess the prevalence of khat use and associated factors among pregnant women in Kersa and Haramaya Health and Demographic Surveillance System Sites, Eastern Ethiopia. Methods: A Community-based cross-sectional study design was employed among randomly selected 1015 pregnant women from an open cohort from Kersa and Haramaya Health and Demographic Surveillance System Sites in Ethiopia. Data were collected through face-to-face interviews from January 30 to April 30, 2021, using Open-Data-Kit (ODK) software, and analysed using SPSS v-26. Descriptive statistics were used to summarize the characteristics of pregnant women. Bivariable and multivariable logistic regression analyses identified factors associated with khat use; an adjusted odds ratio with a 95% confidence interval was estimated. Statistical significance was declared at p<0.05. Results: The prevalence of khat use among pregnant women was 15.5% (95% CI: 13.3, 17.7). Age of the pregnant women, being in the age group between 25 and 35 years, (AOR=2.27, 95% CI: 1.33, 4.89) and 35 years and greater, (AOR=2.33, 95% CI: 1.29, 4.20), having a chronic medical illness (AOR=3.28, 95% CI: 1.27, 8.48) having a history of abortion (AOR=2.87 95% CI: 1.73, 4.76), were significantly associated with khat use among pregnant women. Conclusion: A significant proportion of the women used khat during pregnancy. Age of the pregnant women, history of medical illness and history of abortion were significantly associated with khat use of the pregnant women.